Asian Fermented Herbal Drinks: Traditional Practices, Health Benefits, and Microbial Cultures: Asian Fermented Herbal Drinks: Traditional Practices, Health Benefits, and Microbial Cultures - Peria, Jo Neil T; Pujiati, Pujiati (UNIVERSITAS PGRI MADIUN, 2024)
Asian fermented herbal drinks, rooted in traditional practices, have gained attention for their potential health benefits and cultural significance. These beverages, produced through fermentation of herbs and plant extracts using specific microbial cultures, offer enhanced nutritional and medicinal properties. The fermentation process preserves herbs and transforms their chemical composition, potentially increasing health benefits. This review explores Asian fermented herbal drinks from the Philippines, Indonesia, China, India, Korea, and Southeast Asia. The health benefits, including antioxidant and anti-inflammatory properties, probiotic effects on gut health, anti-cancer and anti-tumor potential, cardiovascular and metabolic health improvements, and immune system support, are discussed. Traditional preparation methods and cultural significance are highlighted, emphasizing fermentation techniques, herbal combinations, and historical context. The role of microorganisms in fermentation is examined, focusing on their contribution to flavor, preservation, and enhancement of functional properties. Despite potential benefits, challenges related to ingredient quality and safety require attention for industrial growth. Integrating traditional knowledge with modern scientific approaches is crucial for developing innovative, health-promoting fermented herbal drinks for local and global markets.